Are Children or Adolescents More at Risk for Posttraumatic Stress Reactions Following Exposure to Violence?: Evidence From Post-Genocide Rwanda. Issue 1 (January 2018) - Neugebauer, Richard; Forde, Allana; Fodor, Kinga E.; Fisher, Prudence W.; Turner, J. Blake; Stehling-Ariza, Tasha; Yamabe, Saori
Abstract : Abstract: Whether children or adolescents exhibit higher levels of posttraumatic stress symptoms (PTSS) in response to violence is an unresolved research question. We examine this issue in UNICEF's 1995 National Trauma Survey (NTS) of 8–19-year-olds ( n = 942) who survived the Rwandan Genocide and lived and attended schools in the community. PTSS were assessed with a symptom checklist based on DSM-IV indexed using an overall score comprising the sum of scores on all items and mean item scores of each of five distinct factors identified in a factor analysis within this sample. Eighty percent of the sample had witnessed massacres; 25%, rape/sexual mutilation. The overall symptom score among children was significantly ( p < 0.05) lower than among adolescents. Among the five separate factors, this direct association of age with symptom levels held for two: re-experiencing ( p < 0.001) and dysphoric arousal ( p < 0.05), but not for the remaining three: avoidance, numbing, and anxious arousal. This discordance in factorial response to violence may help explain prevailing inconsistencies in the age-PTSS association reported to date.